Studies on Iridium(III) Complexes with Ligands Containing Amide Group - Dayakar, G.; Lingaiah, P. (Asian Journal of Chemistry, 2010)
A new series of complexes of iridium(III) with 2-(acetylamino) benzoic acid, 2-(benzoylamino) benzoic acid, 2-(amino benzoyl amino) benzoic acid, 2-[(2-aminophenyl amino) carbonyl] benzoic acid, maleanilic acid, malea-1-naphthalanilic acid, 2-[(phenylamino) carbonyl] benzoic acid have been synthesised and characterised by physico-chemical data.